Evaluation of the effects of platelet-rich fibrin on bone regeneration in diabetic rabbits - BALLI, UMUT; Durmuslar, M. Cenk; Balli, UMUT; Dede, Figen Ongoz; Dogan, Seyma Bozkurt; Misir, A. Ferhat; BARIŞ, EMRE; Yilmaz, Zehra; ÇELİK, HAKAN HAMDİ; Vatansever, Alper (My University, 2016)
Objectives: This study aimed to investigate the effect of platelet-rich fibrin on bone regeneration in critical size defects in the calvaria of diabetic rabbits.